A combined single high-dose rate brachytherapy boost with hypofractionated external beam radiotherapy results in a high rate of biochemical disease free survival in localised intermediate and high risk prostate cancer patients. Issue 2 (November 2016) - Joseph, Nuradh; Taylor, Cathy; O'Hara, Catherine; Choudhury, Ananya; Elliott, Tony; Logue, John; Wylie, James
Abstract: Introduction: Dose escalation has been shown to improve biochemical outcome in localised prostate cancer. An HDR brachytherapy boost is an effective strategy for dose escalation, since it exploits the low α/β ratio in prostate cancer, allowing the delivery of a high biological dose to the tumour. We sought to evaluate the biochemical disease free survival in patients with intermediate and high risk localised prostate cancer treated with EBRT plus HDR brachytherapy as a boost, in our institution. Patients and methods: Biochemical outcome was collected prospectively in 95 patients treated from 2008 to 2010, with an HDR boost of 12.5 Gy followed by EBRT delivered as 37.5 Gy in 15 fractions over 3 weeks. The ASTRO definition of biochemical failure (2 μg/L above PSA nadir) was used as the outcome measure. 61/95 (64%) were classified as high risk (stage > T2b or PSA > 20 μg/L or Gleason score > 7) while 34/95 (36%) were intermediate risk. 92/95 (97%) patients received neoadjuvant androgen deprivation therapy (ADT). Adjuvant hormone therapy was at the discretion of the treating clinician. Results: The median follow-up for the cohort was 65 months (range, 18–88) with a 5-year biochemical DFS of 80.5% (95% Confidence Interval [CI]: 72.8–89.0). The prognostic factors used in the analysis model were: clinical stage, presenting PSA, duration of ADT, Gleason score, risk category, prostate volume, D90 and V100. Only presenting PSA (HR 1.03; CI 1.00–1.05, p  = 0.03) predicted for a poorer biochemical DFS on multivariate analysis. Conclusion: These data confirm that EBRT plus a single-fraction HDR brachytherapy boost achieves good biochemical control in a cohort of predominantly high risk patients.